2014
DOI: 10.33736/ils.1662.2014
|View full text |Cite
|
Sign up to set email alerts
|

Paraphrasing challenges faced by Malaysian ESL students

Abstract: This study examined the challenges faced by Malaysian second language (L2) learners when paraphrasing an academic text. Drawing on interviews with two diploma students from two business majors, I explored the types of challenges they faced when attempting paraphrasing tasks. The findings revealed that the students faced multiple challenges that ranged from text comprehension, poor L2 proficiency to referencing problems. In addition, there were significant differences between paraphrasing strategies adopted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Adi Badiozaman (2014) interviewed two Malaysian L2 students who were taking a diploma program in Business to investigate the difficulties that they encountered when paraphrasing source materials. Students in Adi Badiozaman (2014) study reported copious challenges that they faced when it came to paraphrasing.…”
Section: Difficulties Of Summarizing and Paraphrasing In Academic Wrimentioning
confidence: 99%
See 2 more Smart Citations
“…Adi Badiozaman (2014) interviewed two Malaysian L2 students who were taking a diploma program in Business to investigate the difficulties that they encountered when paraphrasing source materials. Students in Adi Badiozaman (2014) study reported copious challenges that they faced when it came to paraphrasing.…”
Section: Difficulties Of Summarizing and Paraphrasing In Academic Wrimentioning
confidence: 99%
“…These two studies, Flores and Lopez (2019) and Adi Badiozaman (2014), are of great significance as they mark initial attempts to enhance our understanding of the sources of struggles for students when it comes to paraphrasing and summarizing. However, the students who reported such difficulties were pursuing either their bachelor degrees or diploma degrees.…”
Section: Difficulties Of Summarizing and Paraphrasing In Academic Wrimentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, paraphrasing refers to the process of re-delivering the ideas in one's own language. Several researchers defined paraphrasing as the act of restating information by integrating the linguistics features (the semantic and syntactic component) such as synonym substitution, changing the word form, and re-arrange the sentence structure (Kissner, 2006;Badiozaman, 2014). In addition, Driscoll and Brizee (2011) label the term paraphrasing as "your own rendition of essential information and ideas expressed by someone else, presented in a new form" (para.2).…”
Section: Literature Review Basic Concept Of Paraphrasingmentioning
confidence: 99%
“…According to Bailey (2006), "paraphrasing involves changing a text so that it is quite different from the source, while retaining the meaning" (p. 29). Thus, writers must be able to demonstrate an in-depth understanding toward a text before they start to paraphrase certain passage, consider the writers' engagement to the reading passage text (Barry, 2006;Ho, 2010;Liao & Tseng, 2010;Sun, 2012;Badiozaman, 2014). This aims to produce accurate results of paraphrasing by retaining the message from the original excerpt (Badiozaman, 2014)…”
Section: Paraphrasing In Reviewing Literaturementioning
confidence: 99%